CURRENT PROBLEMS OF HISTORY TEACHING IN UZBEKISTAN AND THEORIES OF THE DEVELOPMENT OF THE SCIENCE (American Journal of Research in Humanities and Social Sciences, 2024)
From time immemorial, our country has been an integral part of world civilization, a single geographical region, from the migration of various tribes at different stages of history, the emergence of the first city-states in this region to our modern statehood, and many historical events: wars and massacres, the Islamic Renaissance, the decline of states and khanates from flourishing empires, have taken an indelible place in the pages of our history.